Interworking of a satellite system for mobile multimedia applications with the terrestrial networks. - Priscoli, F.D (IEEE Journal on selected areas in communications)
This paper deals with the interworking of a satellite system for mobile multimedia applications with the terrestrial environment. The concept of an ?overlying network? is introduced with the aim of giving a common approach for the interworking of the considered satellite system with the various terrestrial networks (B-ISDN, N-ISDN, TCP/IP). The paper particularizes the introduced concept to the case in which the considered satellite system is interfaced with the broadband ISDN (B-ISDN)